2018
DOI: 10.1029/2018jd028842
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Synoptic Environment on Rainfall Distribution of Landfalling Tropical Cyclones Over China

Abstract: How the rainfall characteristics of landfalling tropical cyclones (TCs) over China change with the dry-air intrusion is explored through analyzing Tropical Rainfall Measuring Mission (TRMM) and environmental fields. It is found that the rainfall area of landfalling TC is positively correlated to the midlevel environmental relative humidity: the larger the surrounding relative humidity before TC landfall, especially in the southern quadrants of the TC, the larger the rainfall coverage at landfall. Even when sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 59 publications
4
28
0
Order By: Relevance
“…There is no strong preference for the spatial distribution of annual flood peaks with respect to storm tracks (i.e., left or right of the track), even though the records floods caused by tropical cyclones tend to be frequently observed in the leftfront quadrant (typically the down-shear side) of the circulations. This is related to the preferable distribution of extreme tropical-cyclone rainfall, due to enhanced moisture conver-gence and updraft on the down-shear side of the circulation (e.g., Atallah et al, 2007;Shu et al, 2018).…”
Section: Tropical Cyclones and Upper Tails Of Flood Peaksmentioning
confidence: 99%
“…There is no strong preference for the spatial distribution of annual flood peaks with respect to storm tracks (i.e., left or right of the track), even though the records floods caused by tropical cyclones tend to be frequently observed in the leftfront quadrant (typically the down-shear side) of the circulations. This is related to the preferable distribution of extreme tropical-cyclone rainfall, due to enhanced moisture conver-gence and updraft on the down-shear side of the circulation (e.g., Atallah et al, 2007;Shu et al, 2018).…”
Section: Tropical Cyclones and Upper Tails Of Flood Peaksmentioning
confidence: 99%
“…The other 6 tropical cyclones in Table 1 are categorized into the second group (Figure 12 There are no strong preferences for the spatial distribution of annual flood peaks with respect to storm tracks (i.e., left or right of the track), even though the records floods caused by tropical cyclones tend to be frequently observed in the leftfront quadrant (typically the down-shear side) of the circulations. This is related to the preferable distribution of extreme tropical cyclone rainfall, due to enhanced moisture convergence and updraft on the down-shear side of the circulation (e.g., Atallah et al, 2007;Shu et al, 2018). Future studies need to investigate variabilities in the physical properties of river basins (i.e., drainage area, slope, shape) and their relationships with flood peaks (i.e., frequency and magnitude) caused by tropical cyclones, to shed more light on flood hazards associated with landfalling tropical cyclones over China.…”
Section: Tropical Cyclones and Upper Tail Propertiesmentioning
confidence: 99%
“…Previous studies show that landfalling tropical cyclones can make great contributions to extreme rainfall in inland regions, even though the frequency of occurrence is not as comparative as coastal regions (e.g., Zhang et al, 2018a). This is closely linked to a couple of factors, such as the interplay of tropical cyclone and baroclinic disturbances (i.e., known as extratropical transition, Hart and Evans, 2000), interactions with mid-latitude systems (e.g., easterly, Shu et al, 2018;Feng and Shu, 2018), and impact of regional topography (as demonstrated by Typhoon Nina, Yang et al, 2017). The devastating consequences of Typhoon Nina and the August 1975 flood expose inadequacies of conventional approaches for flood frequency analysis (e.g., fitting historical flood records with assumed distribution function), and highlight the importance of hydrometeorological approaches for Probable Maximum Precipitation (PMP) / Probable Maximum Flood (PMF) analyses for better designs of flood-control infrastructures (e.g., Smith and Baeck, 2015;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetries in the TC rainfall associated with landfalling can be modulated by not only VWS [30][31][32][33][34], but also some other factors, such as nonuniform surface features including land-sea contrast and local topographic effect [31,32,[34][35][36][37][38][39] and interaction between TCs and synoptic weather systems [38,40,41]. In general, the landfalling TCs regularly had an asymmetry with a downshear to downshear-left rainfall maximum near the coastal regions, which is consistent with the studies for TCs over the ocean [3,19,42].…”
Section: Introductionmentioning
confidence: 61%
“…Wingo and Cecil [43] noted that strong westerly shear was likely to form more asymmetric rainfall patterns than those of strong easterly shear. Some studies found that the dry air intruded to the right side of the shear vector was more adverse to the TC symmetric circulation [21,38,44,45]. Xu et al [42] presented that the rainfall percentage towards the right quadrant relative to the coastline would exhibit an obvious increase in prelandfall TCs near landfall in the eastern part of USA, which might be induced by the northward recurving of the storm towards the coast where the land-sea roughness gradient is present.…”
Section: Introductionmentioning
confidence: 99%